Pengaruh Inovasi Produk Dan Media Sosial Terhadap Keputusan Pembelian Produk Sepatu Ventela Pada Mahasiswa Feb Umn Al Washliyah Medan - Renaldo Parningotan Sinaga; Indawati Lestari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine and analyze the influence of product innovation and social media on purchase decisions for Ventela shoes among students of the Faculty of Economics and Business (FEB) at Universitas Muslim Nusantara (UMN) Al Washliyah Medan. In the midst of increasingly competitive local footwear industry competition, companies are required to continue innovating and utilizing digital platforms effectively to attract consumer interest. The research method used is a quantitative approach by distributing questionnaires to 88 respondents who are active students of FEB UMN Al Washliyah Medan selected using purposive sampling techniques. Data analysis was performed using multiple linear regression, t-test (partial), F-test (simultaneous), and the coefficient of determination via SPSS software. The results showed that partially, product innovation has a positive and significant effect on purchase decisions with a significance value of 0.001 < 0.05 and t-count 3.406 > 1.988. The social media variable also has a positive and significant effect on purchase decisions with a significance value of 0.001 < 0.05 and t-count 4.106 > 1.988. Simultaneously, product innovation and social media have a significant effect on purchase decisions with an F-count value of 102.174 > 3.10. The Adjusted R Square value of 0.699 indicates that 69.9% of the purchase decision variable can be explained by product innovation and social media, while the remaining 30.1% is influenced by other factors outside this study. The conclusion of this study is that the better the product innovation produced and the more effective the use of social media, the more it will increase consumer purchase decisions.